Cybersecurity disclosure and audit fees: An empirical study of listed companies on the Indonesia stock exchange - Susanto, Susanto; Soepriyanto, Gatot (Edelweiss Applied Science and Technology, 2024)
Cyber attacks on companies cause substantial financial and non-financial losses for all countries, including Indonesia. This empirical study was conducted to identify how cybersecurity risk disclosure (CRD) affects audit fees. This initial study analyzes cybersecurity risk disclosure across all company sectors on the Indonesia Stock Exchange (IDX) list. The current research continues the study of Calderon & Gao (2021) by combining keywords with the research of Li et al. (2018), which were collected manually to extract cybersecurity risk disclosure. During 2019-2023, our sample consisted of 172 companies with 860 observations, and the data obtained is then analyzed using the Stata application. The results show that cybersecurity risk disclosure significantly affects audit fees. This statement indicates that the more words in the cybersecurity risk disclosure, the more the audit fees the company must pay the external auditor tend to increase. When auditors assess a high risk, they need more time to conduct a more in-depth examination so that audit costs increase.